Implementation of the Ecosystem Services Concept in the Environmental Legislation of Ukraine: Current State and Prospects - Suetnov, Evgeny (Problems of legality, 2024)
The article outlines the general principles of the concept of ecosystem services and examines the current state and prospects of its implementation in national environmental legislation. It is established that the need to introduce this concept has already been envisaged by a number of strategic programmatic documents, headed by the “Basic Principles (Strategy) of the State Environmental Policy of Ukraine for the Period up to 2030”, but this concept is still not reflected at the level of key environmental legal acts, in particular, the Law of Ukraine “On Environmental Protection” and resource-specific codes and laws which not only lack any mention of ecosystem services, but also hardly ever use the term “ecosystem” at all. It is proved that one of the ways to implement the concept of ecosystem services in Ukraine is to develop an appropriate legal framework, namely: The Law of Ukraine “On Ecosystem Services” and other related bylaws, which should be done in the near future. At the same time, it is substantiated that in addition to the adoption of new legislation in this area, it is extremely important to analyze the current environmental legislation through the prism of the ecosystem approach and make appropriate changes and additions to it, since only under such conditions can legislative gaps and conflicts be avoided and a coherent model for implementing the concept of ecosystem services be developed, which in the current realities of the armed aggression of the russian federation will help to assess and take into account all the damage caused to the environment of Ukraine.